Gambaran Pelaksanaan Kelas Ibu Hamil Di Wilayah Puskesmas Manisrenggo Klaten - Piscolia Dynamurti Wintoro; Sri Wahyuni (Universitas Muhammadiyah Klaten, 2020)
This Class for Pregnant Women is a means to learn together about health for pregnant women, in the form of face-to-face groups which aims to increase the knowledge and skills of mothers regarding pregnancy, pregnancy care, childbirth, postpartum care, newborn care, myths, diseases. infectious and birth certificate. The class for pregnant women is facilitated by midwives / health workers using the Maternal Kela package, namely the MCH Handbook, flip chart (flipchart), Classroom Implementation Guidelines for Pregnant Women, Handbook for Classroom Facilitators for Pregnant Women and Maternal Gymnastics Book (Kemenkes RI, 2011). The end that is expected from this activity is that every pregnant woman can safely pass the pregnancy, childbirth and childbirth period which will have an impact on reducing the Maternal Mortality Rate (MMR). This research method is descriptive with cross sectional research design. The sample in this study were pregnant women in the third trimester at the Manisrenggo Health Center. The analysis used in this research is univariate analysis. The results of this study were 93.3% were carried out properly according to the questionnaire given. The conclusion of this research is that the implementation of the class of pregnant women in the work area of ​​the Manisrenggo Health Center is mostly good, namely 28 pregnant women (93.3%). Suggestions for health workers at the Puskesmas can work with village cadres to motivate pregnant women to want to attend Pregnant Mothers classes.